Digital human technology in the application of live streaming in social media - Xi Chen; Siva Shankar Ramasamy; Bibi She (Радіоелектронні і комп'ютерні системи)
The subject of this article is the use of Digital Human Technology (DHT) in live broadcasts on social media platforms and its impact on audience engagement and content appeal. This study examines how elements of DHT, such as virtual avatars and AI-driven hosts, are increasingly being used in live broadcasts to improve viewer engagement and retention. The main objective is to evaluate whether the integration of DHT increases viewer engagement, interactivity, and retention, especially compared to traditional streaming methods. This study consists of several key tasks: reviewing the current live DHT landscape, developing a research framework for analyzing engagement metrics, collecting empirical data through surveys and interviews and conducting statistical analysis to identify correlations between DHT use and viewer engagement. The methods used in this study include quantitative approaches such as structured questionnaires to measure viewership indicators and qualitative approaches such as in-depth interviews with streamers and viewers. Statistical methods, such as factor and correlation analysis, are used to assess the impact of DGT on key engagement metrics, such as viewing time, frequency of interaction, and viewer satisfaction. Through systematic observation, this study also captured real-time interactions, providing a comprehensive understanding of DHT effects. The findings emphasize that DHT significantly increases engagement in live broadcasts, providing content creators with innovative ways to retain audiences. However, the high cost of such technology and technical requirements limit its availability to independent streamers. This study provides practical recommendations for streamers and marketers that suggest DHT is a valuable tool for optimizing content appeal and audience engagement. Future research should explore scalable DHT solutions to improve accessibility for a wider range of content creators.